Pengembangan Potensi Manusia dalam Membangun Pendidikan Karakter Perspektif Tasawuf - Ahmad Ali Riyadi; Khoiriyah (Indonesian Journal of Humanities and Social Sciences, 2020)
This study discusses the understanding of the potential possessed by humans in the perspective of Sufism as a foundation for the development and formation of human character. To uncover these objectives, this study uses the method of literature by tracing sufism literature by Sufi figures. Sufism has a significant contribution in the formation of human character. Sufism introduces positive principles that base on human behavior as a source of behavior, a source of movement, a source of normativity, a source of motivation and a source of value that is the reference. Behavioral development can be formed by understanding human character and potential both physically and psychologically. Both of these potentials are the basis for getting to know and manage their environment and know their God.